2022
DOI: 10.1136/bmjopen-2022-065188
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional pain profiling in people living with obesity and attending weight management services: a protocol for a longitudinal cohort study

Abstract: IntroductionPain is prevalent in people living with overweight and obesity. Obesity is associated with increased self-reported pain intensity and pain-related disability, reductions in physical functioning and poorer psychological well-being. People living with obesity tend to respond less well to pain treatments or management compared with people living without obesity. Mechanisms linking obesity and pain are complex and may include contributions from and interactions between physiological, behavioural, psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…However, the worst pain scores did not differ significantly among the various BMI groups (table 5). Several studies have also demonstrated that obesity is associated with increased self-reported pain intensity and severity compared to individuals with normal BMI [25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the worst pain scores did not differ significantly among the various BMI groups (table 5). Several studies have also demonstrated that obesity is associated with increased self-reported pain intensity and severity compared to individuals with normal BMI [25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…This study is a Qualitative Evidence Synthesis. Understanding the lived experience of people living with obesity and/or chronic pain is fundamental to usefully guide health and social policy and inform the planning and implementation of treatment strategies [44][45][46][47][48].…”
Section: Designmentioning
confidence: 99%
“…While Cooper et al 2017 has also provided great insights into the experiences of people overweight and those living with multimorbidity of obesity and CMP, three of the four studies included are now more than a decade old, with several important advancements in the understanding of both pain and obesity in that time. The disease of obesity and disorder of chronic musculoskeletal pain (CMP) are both complex, and weight loss treatments are only a part of the treatment continuum [42][43][44]. Understanding the interaction between these illnesses through the lived experiences of this population is fundamental to establishing what is most meaningful to this population and highlighting further knowledge gaps and treatment opportunities.…”
Section: Introductionmentioning
confidence: 99%